2021
DOI: 10.3390/ijms222212435
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Propionic Acid, a Functional Metabolite of Clostridium sporogenes, Promotes Muscle Tissue Development and Reduces Muscle Cell Inflammation

Abstract: Clostridium sporogenes (C. sporogenes), as a potential probiotic, metabolizes tryptophan and produces an anti-inflammatory metabolite, indole-3-propionic acid (IPA). Herein, we studied the effects of C. sporogenes and its bioactive metabolite, IPA, on skeletal muscle development and chronic inflammation in mice. In the in vivo study, the muscle tissues and serum samples of mice with C. sporogenes supplementation were used to analyze the effects of C. sporogenes on muscle metabolism; the IPA content was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…These studies indicate the protective effect of IPA against neuronal inflammation, which prompted us to select IPA from the metabolites enriched in SER feces as a possible protective substance against SAE. Consistent with previous findings ( 29 , 32 ), we also observed a beneficial role for IPA in SAE, which was related to its anti-inflammatory effects. In the present study, the direct effect of IPA on microglia may be responsible for the reduction in neuroinflammation after IPA treatment.…”
Section: Discussionsupporting
confidence: 92%
“…These studies indicate the protective effect of IPA against neuronal inflammation, which prompted us to select IPA from the metabolites enriched in SER feces as a possible protective substance against SAE. Consistent with previous findings ( 29 , 32 ), we also observed a beneficial role for IPA in SAE, which was related to its anti-inflammatory effects. In the present study, the direct effect of IPA on microglia may be responsible for the reduction in neuroinflammation after IPA treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, IPA acts as a ligand of the aryl hydrocarbon receptor (AhR) present in colonic epithelial cells, activation of which is associated with anti-inflammatory and anticancer effects [119] Interestingly, it has been observed that in patients suffering from colitis serum, IPA concentration decreases significantly [28]. Apart from being an AhR ligand, IPA can also produce its biological action by activating the pregnane X receptor (PXR) present in colonic, liver endothelial and muscle cells [23,119,120]. Complex laboratory techniques allow testing the function of GBB by measuring its permeability to specific substances, including Fluorescein Isothiocyanate-Dextran (FITC-Dextran).…”
Section: Ipa Improves Gut-blood Barrier Functionmentioning
confidence: 99%
“…Interestingly, IPA protects cells from ROS [25,128,129], oxidative damage and lipid peroxidation caused by potassium bromate [130][131][132], potassium iodate [24], iron (II) sulphate [133,134], iron (III) chloride [135], chromium (III) chloride [136], and 2,2 -Azino-bis(3-ethylbenzothiazoline-6sulfonic acid (ABTS) [137]. Additionally, IPA decreases the expression of proinflammatory cytokines, including TNF-α [22,27,121], IL-1β [23,27], IL-6 [27], IL-12 [22], IL-13 [22] and MCP-1 [22,82]. Interestingly, IPA also shows antimicrobial activity by inhibiting the growth of Legionella pneumophila [138,139], and Salmonella typhimurium [140].…”
Section: Ipa Protects Against Oxidative Stress and Attenuates Inflamm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen tolerance in Clostridia may also be beneficial in biomanufacturing, where these strains are used in a number of processes, such as ABE fermentation (focused on C. acetobutylicum) and other bioproduction systems for chemicals and fuels (Moon et al, 2016;Zeng, 2019;Zhao et al, 2020). Focusing specifically on C. sporogenes, this strain has been used for non-acetone forming butanol production from rice straw (Gottumukkala et al, 2013(Gottumukkala et al, , 2015 and has recently been identified as a producer of the potent antioxidant 3-indolepropionic acid (IPA) (Du et al, 2021), which has neuroprotective properties (Zhang and Davies, 2016). The use of Clostridium has been limited in these contexts due to the requirement of an oxygen-free environment.…”
Section: Discussionmentioning
confidence: 99%